Awareness, perception and utilization of a mobile health clinic by people who use drugs. (31st December 2022) - Grieb, Suzanne M.; Harris, Robert; Rosecrans, Amanda; Zook, Katie; Sherman, Susan G.; Greenbaum, Adena; Lucas, Gregory M.; Page, Kathleen R.
Abstract: Introduction: People who use drugs (PWUD) face a multitude of barriers to accessing healthcare and other services. Mobile health clinics (MHC) are an innovative, cost-effective health care delivery approach that increases healthcare access to vulnerable populations and medically underserved areas. There is limited understanding, however, of how PWUD perceive and experience MHCs. Methods: Semi-structured interviews were conducted with 31 PWUD – 16 who had received care (clients) on an MHC (The Spot) and 15 who had not (non-clients) – to explore their perceptions and utilization of an MHC partnered with a mobile syringe services program in Baltimore, Maryland. Data analysis of the text was conducted using an iterative thematic constant comparison process informed by grounded theory. Results: Clients and non-clients, once aware of the MHC, had positive perceptions of The Spot and its benefits for their individual health as well as for the wellbeing of their community. These sentiments among clients were largely driven by access to low-barrier buprenorphine and service delivery without stigma around drug use. However, lack of general awareness of the spot and specific service offering were barriers to its use among non-clients. Discussion: MHCs provide an important opportunity to engage PWUD in healthcare and to expand buprenorphine use; however, even with accessibility near where PWUD access injection equipment, barriers to its use remain. Peer dissemination may be able to facilitate program information sharing and recruitment. KEY MESSAGES: People who use drugs perceive a mobile health clinic in their neighbourhood as a benefit to their communities and themselves by improving access to healthcare services, providing access to low-threshold buprenorphine dispensation, and offering services without drug use stigma. People who use drugs learned about a mobile health clinic in their neighbourhood largely through word-of-mouth. As a result, people received limited information about the mobile health clinic services creating a barrier to its use.